MULTICULTURALISM IN ISLAMIC CIVILIZATION DURING THE CLASSIC PERIOD - Abdurrahman, Dudung (ADDIN, 2017)
The main objectives of this study are to map and analyze the multiculturalism pattern in Muslim civilization history during the period. Analyses are developed with historical and socio-cultural perspectives. Several patterns of multiculturalism in Islamic civilization are found: Firstly, during the Prophet and al-Khulafa ar-Rasyidun era, Islam–as a doctrine and religion system–had accomodative patterns to the cultural form in al-'ashabiyyah al-qabaliyyah tradition and began to perform as Arabic culture-based civilization. Secondly, during the Daulah Umayyah era, disregarding that the civilization was developed using Arabic politics, the policies regarding Islamic expansion encouraged acculturation of Arabic-Muslim and non-Arabic or non-Muslim communities, leading to the multiculturalism in Islam at that time. Finally, during the Daulah Abbasiyah era, multiculturalism became more obvious as a pattern of Islamic civilization, indicated by the roles of non-Arabic cultures in Islamic civilization development.